Combination of isocitrate dehydrogenase 1 (IDH1) mutation and podoplanin expression in brain tumors identifies patients at high or low risk of venous thromboembolism. (20th May 2018) - Mir Seyed Nazari, P.; Riedl, J.; Preusser, M.; Posch, F.; Thaler, J.; Marosi, C.; Birner, P.; Ricken, G.; Hainfellner, J. A.; Pabinger, I.; Ay, C.
Abstract : Essentials Risk stratification for venous thromboembolism (VTE) in patients with brain tumors is challenging. Patients with IDH1 wildtype and high podoplanin expression have a 6‐month VTE risk of 18.2%. Patients with IDH1 mutation and no podoplanin expression have a 6‐month VTE risk of 0%. IDH1 mutation and podoplanin overexpression in primary brain tumors appear to be exclusive. Summary: Background: Venous thromboembolism (VTE) is a frequent complication in primary brain tumor patients. Independent studies revealed that podoplanin expression in brain tumors is associated with increased VTE risk, whereas the isocitrate dehydrogenase 1 (IDH1) mutation is associated with very low VTE risk. Objectives: To investigate the interrelation between intratumoral podoplanin expression and IDH1 mutation, and their mutual impact on VTE development. Patients/Methods: In a prospective cohort study, intratumoral IDH1 R132H mutation and podoplanin were determined in brain tumor specimens (mainly glioma) by immunohistochemistry. The primary endpoint of the study was symptomatic VTE during a 2‐year follow‐up. Results: All brain tumors that expressed podoplanin to a medium‐high extent showed also an IDH1 wild‐type status. A score based on IDH1 status and podoplanin expression levels allowed prediction of the risk of VTE. Patients with wild‐type IDH1 brain tumors and high podoplanin expression had a significantly increased VTE risk compared with those with mutant IDH1 tumors and no podoplanin expression (6‐month risk 18.2% vs. 0%). Conclusions: IDH1 mutation and podoplanin overexpression seem to be exclusive. Although brain tumor patients with IDH1 mutation are at very low risk of VTE, the risk of VTE in patients with IDH1 wild‐type tumors is strongly linked to podoplanin expression levels.